Hacia un nuevo currículum de física y química para el bachillerato : una consulta al profesorado - Universidad de Valencia, Seminario permanente de Física y Quími (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The test consists in a questionnaire about basic criteria in order [o estabiish a Physics and Chemistry curriculum, which leads to know the teachers' orientations and to analyse the different proposals of the currimulum itself later on.